Controlling the Magnetization Reversal in Planar Nanostructures with Wire-Ring Morphology - Lopez-Cabrera, C; Escrig-Murua, J; Palma-Solorza, J; Corona-Gonzalez, R (American Institute of Physics, 2014)
Magnetization reversal in planar nanowires has been controlled using structures with a larger area pad connected to a nanowire or by means of patterned variations in the planar nanowire such as notches. In this letter, we have introduced a magnetic nanostructure defined as a planar nanostructure with wire-ring morphology. In particular, we have performed micromagnetic simulations to investigate how the magnetic properties (coercivity and remanence) change as a function of the geometric parameters of the nanostructure. Additionally, we observe that when the ring is very thin, the system reverses its magnetization by nucleation and propagation of domain walls along the nanowire. Conversely, when the ring has very thick walls, or directly turns into a solid cylinder, the system nucleates a vortex in the ring/cylinder, and then propagates the domain walls toward the nanowire sections. This reversal process is characterized by a step or plateau in the hysteresis curve, that is, a region in which differential magnetic susceptibility presents a local minimum or, ideally, vanishes. Finally, this nanostructure can be used in many potential applications related to the control of domain walls in planar nanowires. © 2014 AIP Publishing LLC.